Novel Electrochemical Biosensors for Clinical Assays - Guerrieri, Antonio (MDPI, 2021)
Biosensors, i.e., devices where biological molecules or bio(mimetic)structures are intimately coupled to a chemo/physical transducer for converting a biorecognition event into a measurable signal, have recently gained a wide (if not huge) academic and practical interest for the multitude of their applications in analysis, especially in the field of bioanalysis, medical diagnostics, and clinical assays. Indeed, thanks to their very simple use (permitting sometimes their application at home), the minimal sample pretreatment requirement, the higher selectivity, and sensitivity, biosensors are an essential tool in the detection and monitoring of a wide range of medical conditions from glycemia to Alzheimer’s disease as well as in the monitoring of drug responses. Soon, we expect that their importance and use in clinical diagnostics will expand rapidly so as to be of critical importance to public health in the coming years. This Special Issue would like to focus on recent research and development in the field of biosensors as analytical tools for clinical assays and medical diagnostics.